Studies on water consumption, night grazing and growth of Boran crossbred steers at Kongwa, Tanzania - Wigg, P.M; Owen, M.A. (1973)
In a comparison of water intake of Boran and Angus-Boran steers over three years, the crossbreds consumed more water per head than the Borans, particularly during the hotter months. There was little difference between the groups on the basis of intake per unit liveweight, and intake per unit liveweight decreased with increasing maturity. The provision of night grazing increased liveweight of Boran and Angus-Boran steers by 5.5 and 6.1 per cent liveweight respectively. The crossbred steers maintained or slightly increased their initial weight advantage over the Boran in both traits, but overall difference was only 5.2 and 3.4 per cent in the water consumption and night grazing traits respectively fluctuations in liveweight than the Borans.